2013
DOI: 10.3390/rs6010135
|View full text |Cite
|
Sign up to set email alerts
|

A Phenology-Based Classification of Time-Series MODIS Data for Rice Crop Monitoring in Mekong Delta, Vietnam

Abstract: Rice crop monitoring is an important activity for crop management. This study aimed to develop a phenology-based classification approach for the assessment of rice cropping systems in Mekong Delta, Vietnam, using Moderate Resolution Imaging Spectroradiometer (MODIS) data. The data were processed from December 2000, to December 2012, using empirical mode decomposition (EMD) in three main steps: (1) data pre-processing to construct the smooth MODIS enhanced vegetation index (EVI) time-series data; (2) rice crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 37 publications
3
104
0
Order By: Relevance
“…We found good agreement in the spatial distribution of single, double and triple rice-cropping schemes compared to previous studies in the Mekong Delta that reported cropping scheme maps with accuracies similar to our product [6,8,49,66,77]. The major driving force behind a farmer's choice of cropping scheme is the availability and management of water [66].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…We found good agreement in the spatial distribution of single, double and triple rice-cropping schemes compared to previous studies in the Mekong Delta that reported cropping scheme maps with accuracies similar to our product [6,8,49,66,77]. The major driving force behind a farmer's choice of cropping scheme is the availability and management of water [66].…”
Section: Discussionsupporting
confidence: 64%
“…We suspect that these dynamic changes are also one of the error sources contributing to the low producer accuracy of the single-cropped class compared to the 2005´2010 intersection. Single-cropped, rainfed rice is increasingly diminished in favor of more profitable shrimp and fish farming [8,66,78] and could thusly be misclassified when such a change occurred during our study period. In addition, this cropping scheme is less widely distributed and spatially homogeneous than double or triple crop rice and might therefore be underrepresented in the 2005 land-use map which is based on moderate resolution data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations